Financial Performance Analysis of Bank Aceh's During the Covid-19: RGEC Approaches - Ibrahim, Azharsyah; Muksal, Muksal; Sartika, Ayu (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
The Covid-19 pandemic has had a significant impact on various sectors in Indonesia, including the banking industry. This study aims to compare the financial performance of PT Bank Aceh Syariah before and during the Covid-19 pandemic using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) analysis method. Secondary data used in this research were obtained from the financial statements of Bank Aceh Syariah published on the bank's official website. Data analysis was conducted using the independent sample t-test hypothesis testing. The results indicate that there were no significant differences in the ratios of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and Capital Adequacy Ratio (CAR) between the periods before and during the Covid-19 pandemic. These findings suggest that Bank Aceh Syariah has been able to maintain its financial performance despite the challenges posed by the pandemic. This study contributes to the understanding of the resilience and adaptability of Islamic banks in the face of economic shocks and highlights the importance of robust risk management and governance practices in ensuring financial stability during times of crisis.